Evidence-based practices and treatments for children with autism - Reichow, Brian; Doehring, Peter; Cicchetti, Domenic V.; Volkmar, Fred R. (Springer, 2011)
Autism spectrum disorders (ASDs) have been increasingly diagnosed in recent years and carries with it far reaching social and financial implications. With this in mind, educators, physicians, and parents are searching for the best practices and most effective treatments. But because the symptoms of ASDs span multiple domains (e.g., communication and language, social, behavioral), successfully meeting the needs of a child with autism can be quite challenging. Evidence-Based Practices and Treatments for Children with Autism offers an insightful and balanced perspective on topics ranging from the historical underpinnings of autism treatment to the use of psychopharmacology and the implementation of evidence-based practices (EBPs). An evaluation methodology is also offered to reduce the risks and inconsistencies associated with the varying definitions of key autism terminology. This commitment to clearly addressing the complex issues associated with ASDs continues throughout the volume and provides opportunities for further research. Additional issues addressed include: Behavioral excesses and deficits treatment Communication treatment Social awareness and social skills treatment Dietary, complementary, and alternative treatments Implementation of EBPs in school settings Interventions for sensory dysfunction With its holistic and accessible approach, Evidence-Based Practices and Treatments for Children with Autism is a vital resource for school psychologists and special education professionals as well as allied mental health professionals, including clinical child and developmental psychologists, psychiatrist, pediatricians, primary care and community providers.